The stability mechanism of Pickering emulsions fabricated by multi-functional amylose-based nanoparticles in a delivery system. Issue 5 (24th February 2023) - Wang, Pingping; Wang, Yang; Chen, Chun; Fu, Xiong
Abstract : In this work, multi-functional amylose-based nanoparticles (OSA-AM-9/VE NPs) were fabricated via simple and sustainable esterification, encapsulation, and co-precipitation processes of amylose (AM), octenyl succinic anhydride (OSA), and vitamin E (VE). Abstract : In this work, multi-functional amylose-based nanoparticles (OSA-AM-9/VE NPs) were fabricated via simple and sustainable esterification, encapsulation, and co-precipitation processes of amylose (AM), octenyl succinic anhydride (OSA), and vitamin E (VE). These nanoparticles showed a nanometer size of 243.2 nm and a regular spherical shape which contributed to their excellent physical and oxidative stability and the outstanding pH-responsive performance of a Pickering emulsion. Compared with OSA-AM-9 and OSA-AM-9 NPs, the Pickering emulsion stabilized by OSA-AM-9/VE NPs presented higher stability and stronger antioxidant capacity. The delivery system of the OSA-AM-9/VE NP stabilized emulsion could protect fish oil from gastric juice and then was digested to facilitate the absorption of ω-3 polyunsaturated fatty acids in the intestine due to the pH-induced protonation/deprotonation of carboxyl groups in OSA-AM-9/VE NPs.